STUDI POTENSI AIR TANAH MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER DAN WENNER DI KAMPUNG NAMBON KABUPATEN JAYAPURA - Zakaria Victor Kareth; Kezia Noviani Anou (JFT : Jurnal Fisika dan Terapannya, 2022)
Kampung Nambon is a village in Jayapura regency which has no access to clean water. Groundwater is an alternative water source for villages which are prone to surface water sources. Groundwater aquifers are porous and permeable subsurface layers which can hold and transmit groundwater. Geoelectric method is a common geophysical method for groundwater exploration due to direct relationship between resistivity and water content. The objective of this study is to characterize subsurface structure of Kampung Nambon and to estimate the depth of potential groundwater aquifer using Vertical Electrical Sounding (VES) of Schlumberger array and Electrical Resistivity Tomography (ERT) of Wenner array. An ERT line of 100 metres whose midpoint is the sounding point of VES with maximum electrode spacing (AB/2) of 250 metres were performed. The results show that subsurface at Kampung Nambon is heterogeneous with significant lateral variation where karst formation was estimated at depth range of 5 – 15 meters. This karst formation might contain groundwater flow as indicated by relatively low resistivity values compared to high resistivity background of Limestone from Jayapura formation (Qpj).